GENERATION Z CAREER OPTIONS IN THE GOVERNMENT SECTORIN THE TOURISM SECTOR WITH THE PRESENCE OF THE GENERATION X MINISTERAS A MODERATING VARIABLE - Supina, Supina (Journal of Indonesian Tourism and Policy Studies, 2020)
This study aims to see whether there is a change in the phenomenon with the presence of the Minister of Tourism from Generation X who has the closest age gap to Generation Z, it aims to see if the election of this millennial minister can increase Generation Z's interest in choosing a career in the tourism sector government, to optimize the demographic bonus in the future. This is a descriptive approach method research. The results of this study indicates that the presence of the Minister of Tourism from Generation X is able to strengthen the relationship between Generation Z Career Options to be State Civil Service in the Tourism Sector, and there are also another findings, which can strengthen and weaken Generation Z's desire to have a career in government